Molecular characterization of methicillin-resistant staphylococci among apparently healthy students - Ogefere, Helen Oroboghae; Ogunleye, Lawrence Ayodele (Faculty of Medicine, Trisakti University, 2019)
BackgroundStaphylococcus aureus are widely considered a major factor of nosocomial and community-acquired infections. This work was aimed at determining the prevalence of methicillin-resistant S. aureus (MRSA) among apparently healthy students. MethodsA cross-sectional study was conducted involving 400 nasal swab samples randomly collected from students using sterile swab sticks and processed to recover S. aureus using standard microbiological techniques. Conventional methods were used to identify the isolates and antibiotic susceptibility tests were performed using Kirby-Bauer disc diffusion method according to performance standards of Clinical and Laboratory Standard Institute guidelines. Methicillin-resistance was detected phenotypically using cefoxitin 30Âµg discs. Bacterial deoxyribonucleic acid (DNA) extraction was done on cefoxitin-resistant staphylococci isolates only using ZymoResearch (ZR) fungal/bacterial DNA MiniPrepTM kit. A polymerase chain reaction assay targeting the 16S rRNA, nuc, and mecA genes on 1.0% agarose gel electrophoresis stained with ethidium bromide was used to identify S.aureus and detect methicillin resistance. ResultsThe overall prevalence of MRSA was 5.8% using phenotypic methods. PCR amplification of the 23 phenotypically confirmed MRSA using 16S rRNA and nuc genes identified staphylococci 23/23(100%) and S. aureus 23/23(100%) at band size 886bp and 225bp respectively. However, 16(69.6%) were positive for mecA gene at band size 532bp by PCR method. Poor level of susceptibility was recorded among the MRSA namely to erythromycin (26.6%), cloxacillin (0%), augmentin (0%), cefuroxime (0%), ceftriaxone (0%) and ceftazidime (0%). Ofloxacin was the most effective antibiotic (60.9%). ConclusionActive antimicrobial surveillance of pathogenic staphylococci is important to analyze the infections and transmission rate for possible control measures.